PENGARUH KOMITMEN DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT. BINTOMO PROPERTI INDONESIA - Lengga Pramu Lestari; Eman Sulaeman; Danang Kusnanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of commitment and work discipline on employee performance at PT. Bintomo Properti Indonesia. The research method used is descriptive verification with a quantitative approach, with the data sources used in this study are primary data and secondary data, namely questionnaires and bibliography. The research sample was 105 employees, using non-probability sampling technique. The analysis used is path analysis and hypothesis testing using t test and F test. The results of this study indicate that the commitment variable based on the results of the questionnaire is obtained with a mean of 344.1, this shows that the average respondent's answer is in the criteria of moderately agree, the work discipline variable based on the results of the questionnaire is obtained with a mean of 341.5, this shows that is in the criteria of moderately agree, the employee performance variable based on the results of the questionnaire is obtained with a mean of 340.4, this means that the average employee's answers are in the criteria of moderately agree. The results of hypothesis testing there is a correlation between commitment and work discipline of 0.748, which means that there is a strong correlation. The results of the partial hypothesis test that commitment has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance. The results of the simultaneous hypothesis that commitment and work discipline simultaneously have a significant effect on employee performance. The r2 test for commitment and work discipline on employee performance obtained R Suare of 0.902, meaning that 90.2% of employee performance was influenced by these two variables, while 9.8% of employee performance was influenced by other variables not examined in this study.